Analisis Penerapan Media Papan Buah Cerdas Terhadap Peningkatan Motivasi Belajar Matematika Siswa Kelas 3 SD - Rohmah, Tri Iftitahur; Nugraini, Mei Laila; Safitri, Nafilah; Rahmawati, Elyani; Masfuah, Siti (Papanda, 2025)
Elementary school students' learning matematic motivation, especially in the lower grades, is often low due to less interactive learning methods. This study aims to analyze the use of Smart Fruit Board media on the learning matematic motivation of grade III elementary school students on data presentation materials. The study used a descriptive qualitative method with observation, interview, documentation, and questionnaire techniques. The subjects of the study included teachers and grade III students of SD 1 Bae. The results showed that this media was effective in increasing students' interest, participation, and positive attitudes. Expert validation showed high feasibility in terms of material, design, technical, and ease of use. Student responses were also very positive, especially in terms of appeal, involvement, and motivation. Smart Fruit Board media has proven to be an effective alternative in creating fun and meaningful learning.